Sociology 160 Principles of Sociology - Ore, Tracy (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In the coming weeks, you will find that this course relies heavily on communication. This syllabus is provided to you as a means of beginning and facilitating this process. In the following pages, I share some of the bases for my teaching philosophy as well as my expectations of you in this course.